Linkages between Investment Potential and Quality of Educational Institutions: Evidence from India. (9th January 2023) - Prakash, Puneet
Abstract : Using disparate datasets, one on the quality of higher education institutions (HEIs) in India comprising 348 HEIs that were accredited over the years 2004–2008, and another on the investment potential of states based on four indicators, we fail to find a correlation between the investment potential of a state and the mean efficiency of its HEIs computed using nonparametric data envelopment analysis (DEA). However, interactions of investment potential indicators with HEI scores on seven quality assessment criteria exhibit a significant impact on efficiency scores thereby suggesting a latent moderating effect. We conclude that the investment potential moderates the quality assessment of HEIs, but these indicators do not affect the efficiency of HEIs. A direct policy implication of the study is a latent link between HEI quality and investment potential of a state but not an overt one. Moreover, a state's infrastructure interacts with teaching and learning to affect HEI efficiency positively, whereas research output and good political governance interact to affect efficiency positively and significantly.